Comparison of Perceptions of Students and Academicians on Generation Y Characteristics - Nihal Ünaldı Baydın; Oznur Ispır; Ramazan Emiralioğlu; Sevilay Aydın (Sağlık ve Hemşirelik Yönetimi Dergisi, 2020)
INTRODUCTION: AIM: This study aimed to examine nursing students' self-assessments and academicians' assessments of them in terms of Generation Y characteristics and to compare them perception. It used a descriptive and correlational research design. METHODS: METHODS: The sample of this study consisted of 422 students and 75 academicians in the faculty of nursing at a state university in the 2016-2017 academic year. The data were collected using an Introductory Information Form and the Teachers' Perceptions of Generation Y Student Characteristics Scale. The data were analyzed with using descriptive analyses, the t-test, the Mann-Whitney U test and the Kruskal-Wallis test. RESULTS: RESULTS: This study found that the students' total mean score on the scale was 3.83+-0.49, while the academicians' was 3.00+-0.48. The self-assessments of students were slightly higher than the assessments of academicians, but the difference was not significant. In terms of the perceptions about Generation Y regarding students, the academicians were found to assess students at the lowest level in the orientation toward work subdimension, while the students were found to assess themselves at the lowest level in the orientation toward learning subdimension. DISCUSSION AND CONCLUSION: CONCLUSION: Results of the study shows that the assessments of students and academicians in terms of the Generation Y characteristics of students were at the moderate levels and similar.